Economics transformed : discovering the brilliance of Marx - Albritton, Robert, 1941- (Pluto Press, 2007)
Robert Albritton brings to life the classic concepts in Marx's economic thought. As well as examining these essential points of Marxist theory, he shows that they offer great potential for further study. Deeply critical of the way economics is taught and studied today, this is a textbook that will appeal to anyone who wants a forward-thinking approach to the discipline that's free from the constraints of neo-classical orthodoxy. Taking up key aspects of Marx's work, including surplus value theory, dialectical reasoning and the commodity form, Albritton highlights their relevance in the modern world -- and explains why mainstream economics has been so blind to their revolutionary potential. Written with style and clarity, it is perfect for economics undergraduates.